Enhancing Individual Taxpayer Compliance in Indonesia: Determinants of Using Population Identification Number as Taxpayer Identification Number - Margono, Toni Aris; Ilmi, Muhammad Bahrul (Journal of Accounting and Investment, 2025)
Research aims: This study aims to empirically examine the direct effect of socialization, sanctions, awareness and knowledge on individual taxpayer compliance in Indonesia. Design/Methodology/Approach: The methodology is a survey utilizing a random sample. The survey comprised 91 individual taxpayers as respondents. This research employs multiple linear regression analysis utilizing SPSS as the analytical instrument.Research findings: The results showed that socialization, sanctions, and awareness positively affected taxpayer compliance. In contrast, knowledge does not influence taxpayer compliance. Theoretical contribution/ Originality: This research provides an understanding of the factors that influence taxpayer compliance. In addition, this research topic is still relatively new in Indonesia.Practitioner/Policy implication: This research can be used to determine the driving factors of individual taxpayer compliance so that it can be used as input and consideration on the rules for using PIN as TIN. Research limitation/Implication: This research can be a source of new ideas on future research topics. Additionally, this research can serve as a guide for utilizing PIN as a TIN to enhance taxpayer compliance.